The role of energy metabolism in driving disease progression in inflammatory, hypoxic and angiogenic microenvironments - Phelan, James (My University, 2015)
Cellular metabolism plays a crucial role in primed inflammatory, hypoxic and angiogenic microenvironments by supporting disease progression in a range of disease entities. To adapt to fluctuating stress-induced microenvironments, pre-neoplastic and neoplastic tissue must utilise a diverse range of molecular mediators to alter their metabolism. Despite being widely documented to play independent roles in disease prevalence, these complex processes exploit a range of key cellular components that act in tandem to restore metabolic equilibrium. Therefore, this review examines the primary molecular mechanisms linking energy metabolism with inflammation, hypoxia and angiogenesis. Furthermore, the review considers a diverse range of conventional and novel mediators that link energy metabolism and hypoxia. Moreover, to investigate their reciprocal relationship and the mechanisms employed to execute their functional effect in greater detail, the roles of glycolysis and oxidative phosphorylation in rheumatoid arthritis and circadian rhythms respectively are reviewed. Lastly, this review explores some current metabolic-based treatments and multi-targeted therapies that could potentially target these fundamental cellular processes.
PUBLISHED
Keywords: Energy metabolism; Inflammation; Hypoxia; Angiogenesis; Cancer; Health